Edukasi Kesehatan Remaja Pada Siswa MA AL Hidayah Duminanga - Ahlan Sangkal; Adelia Zahra Manueke; Nadyrah Nurul Hidayat; Sri Delviana Daud; Rosalia Katili; Putri Tarisa Mangkat; Annisa D.P Nurhamidin (PT. ALHAFI BERKAH INDONESIA, 2023)
Real Work Lecture (KKN) is a form of learning in the form of community service carried out by a group of students in order to promote community welfare and educate the nation's life. Madrasah Aliyah Al-Hidayah Duminanga is one of the schools where the Community Service Program (KKN) is held by the Muhammadiyah University of Manado, Faculty of Health Sciences. The implementation of KKN this year is more focused on high schools than serving the community. The aim is to increase students' knowledge about the world of health more broadly and students can apply healthy living practices in daily activities that can have an impact on themselves and the surrounding environment. For this reason, observations were made to identify problems found in the field that occurred at MA Al-Hidayah Duminanga. Observation is a data collection technique in which the researcher makes observations, either directly or indirectly, about the things being observed and records them on an observation tool. In determining a problem, the method used is to determine the priority of the problem qualitatively. Based on observations that were made for one week starting from February 21-25, several problem factors were found at Madrasah Aliyah Al-Hidayah Duminanga, namely a lack of knowledge in terms of mental health, lack of attention to environmental hygiene, and also the absence of UKS facilities. The solution offered to activity partners is to conduct counseling and education about the importance of adolescent mental health (online game addiction, the dangers of smoking, & being wise in social media) as well as reproductive health education, the dangers of promiscuity and also education on proper drug use. Suggesting guidance and rehabilitation in schools such as the role of guidance and counseling teachers who have been student counselors at schools directing students with indications of unfavorable behavior such as personal, family and rehabilitation approaches.